2008
DOI: 10.1111/j.1525-139x.2008.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

NON‐CORONARY HEART DISEASE IN DIALYSIS PATIENTS: Hypertrophy and Fibrosis in the Cardiomyopathy of Uremia—Beyond Coronary Heart Disease

Abstract: Cardiac disease is the leading cause of death in uremic patients. In contrast to previous opinion, coronary events account for a relatively small proportion of cardiac deaths, the most common causes being sudden death and heart failure. Against this background the current text will discuss noncoronary cardiac pathology, specifically the pathogenesis and the morphological findings caused by (pathological) cardiac hypertrophy, cardiac interstitial fibrosis and microvascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
139
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 180 publications
(196 reference statements)
3
139
1
8
Order By: Relevance
“…Such cardiomyopathy occurs very early in the course of impaired renal function, both in experimental studies (10) and in human observations. It is characterized by a composite of inappropriate ventricular hypertrophy, marked interstitial fibrosis, microvessel disease with thickening of intramyocardial arteries, and capillary deficit (11). In a small biopsy controlled study, it was shown that cardiac fibrosis was a predictor of death (12).…”
Section: Underlying Cardiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Such cardiomyopathy occurs very early in the course of impaired renal function, both in experimental studies (10) and in human observations. It is characterized by a composite of inappropriate ventricular hypertrophy, marked interstitial fibrosis, microvessel disease with thickening of intramyocardial arteries, and capillary deficit (11). In a small biopsy controlled study, it was shown that cardiac fibrosis was a predictor of death (12).…”
Section: Underlying Cardiac Diseasementioning
confidence: 99%
“…In a small biopsy controlled study, it was shown that cardiac fibrosis was a predictor of death (12). Cardiac fibrosis (causing arrhythmia as a result of reentry circuits) as well as diastolic malfunction (the result of reduced compliance [11]) are the most important causes of cardiac death and potentially future therapeutic targets.…”
Section: Underlying Cardiac Diseasementioning
confidence: 99%
“…More than 60% of all cardiac deaths in dialysis patients are attributable to sudden cardiac death and/or arrhythmias (1). Many factors are likely operative in mediating the high cardiac risk seen in dialysis patients and include factors related to underlying diseases (hypertension, diabetes mellitus) and uremia (myocardial fibrosis) (2)(3)(4)(5). In patients treated with hemodialysis (HD), the long interdialytic interval and the myocardial stunning induced by the HD procedure may possibly be additional contributing factors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Several cardiovascular disease therapies effective in the general population have been entirely ineffective in patients on hemodialysis (HD). However, cardiovascular disease in patients on dialysis is not solely caused by traditional risk factors or the uremic milieu (1). HD itself causes recurrent and cumulative ischemic injury to the heart, brain, and other organs (2).…”
Section: Introductionmentioning
confidence: 99%